Digitalisasi Manajemen Aset melalui Aplikasi Inventory sebagai Upaya Peningkatan Tata Kelola Organisasi Masyarakat - Teofilus Sunarsa; Anis Choirunnisa; Tita Latifah Ahmad; Hagi Sugara Putra; Febri Nabilah (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
This community service aims to implement a digital asset management system based on website and Android for community organizations. This system is designed to overcome manual governance barriers such as data loss and cost inefficiency. The methodology includes field observation, problem identification, and user interface design. The result is an inventory application that enables real-time and systematic asset monitoring. The conclusion shows that the application has successfully improved administrative order and facilitated access to asset information for both management and members.